2022
DOI: 10.1002/aenm.202200966
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Activation of V4+/V5+ Redox Couples in NASICON Phosphate Cathodes

Abstract: Na-ions batteries (NIBs) is greatly hindered by the limited capacity delivery and voltage output due to the high redox potential of Na + /Na and large radius of Na + ions. [1][2][3][4][5] Among the previously exploited cathode materials for NIBs, the polyanion-type cathodes with a Na superionic conductor (NASICON) structure proposed by John B. Goodenough since 1976 have received extensive interests, considering their robust 3D framework, unique inductive effect and thereby enhanced comprehensive performance. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 48 publications
(95 reference statements)
4
63
0
Order By: Relevance
“…When charged to 3.7 V, two peaks of V 3+ shift to 524.7 and 517.3 eV, matching well with the oxidation of V 3+ to V 4+ . 43 When further charged to 4.2 V, the above peaks further shift to 525.0 and 517.7 eV, matching well with the further oxidation of V 4+ to V 5+ .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…When charged to 3.7 V, two peaks of V 3+ shift to 524.7 and 517.3 eV, matching well with the oxidation of V 3+ to V 4+ . 43 When further charged to 4.2 V, the above peaks further shift to 525.0 and 517.7 eV, matching well with the further oxidation of V 4+ to V 5+ .…”
Section: Resultssupporting
confidence: 61%
“…During the charging/discharging process, only Na2 can be reversibly extracted/intercalated in the Na-O polyhedron with zigzag diffusion routes Na2 → Na1 → Na2. 43 The area of bottleneck gradually shrinks with the release of Na + from 3.25 to 1 (Supporting Information: Table S7), indicating a severer volume shrinkage when V 4+ is further oxidized to V 5+ , making it more difficult for Na + to diffuse. When the Na content is 1.25, the bottleneck area is minimized due to the Jahn-Teller effect leading to abnormal lattice distortion.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, part of them has good reversible V 4+ /V 5+ redox couples. Xu et al 105 proposed a low-cost strategy of Fe 2+ doping into Na 3+x V 2−x Fe x (PO 4 ) 3 (NVFP-x, x = 0, 0.2, 0.4 0.6, 0.8, and 1.0) to activate V 4+ /V 5+ redox to achieve promising capacity (e.g., the best capacity of NVFP-0.4: ∼113 mAh g −1 at 20C) (Figure 7a) and further revealed that V 4+ /V 5+ can be reversibly activated only when V-based compounds have sufficient relative content of Na (2). In all of the samples shown in Figure 7b, low-content Fe-doped NVFP-x (0 < x ≤ 0.4) can better reversibly activate V 4+ /V 5+ redox, because its extra x mol Na + prefers to occupy the Na(2) site, resulting in higher Na(2) uptake.…”
Section: Ion Doping At V Site 421 Low-priced and Parity-priced Ion Do...mentioning
confidence: 99%
“…(c) The operando XRD contour map of NVFP-0.4 electrode collected at a selected angle range. Reproduced with permission from ref . Copyright 2022 John Wiley and Sons.…”
Section: Foreign Ion Dopingmentioning
confidence: 99%
“…In terms of the chemical and crystal structure of NVP, the building blocks include tetrahedral [PO 4 ], octahedral [VO 6 ] and inserted Na + -ions. 33–36 While Na + and V 3+ components are the sites responsible for Na + -ion storage capability, anionic phosphate (PO 4 3− ) is electrochemically inactive during battery cycling and inert for providing capacity. 37–39 Substituting inert PO 4 3− with tetrahedral redox-active anions within the NVP matrix could improve the material capacity and maintain the crystal structure at the same time.…”
Section: Introductionmentioning
confidence: 99%